Adhesion properties of the hybrid system made of laser-structured aluminium EN AW 6082 and CFRP by co-bonding-pressing process - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Relationship between laser-generated micro- and nanostructures and the long-term stability of bonded epoxy-aluminum joints - Freund, Jonathan; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; de los Arcos, T.; Kollmann, S.; Carlet, M. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Testing, modelling, and parameter identification for adhesively bonded joints under the influence of temperature - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik; Hein, David; Steinmann, Paul (Journal of Adhesion Science and Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas D.; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Synthesis and Characterization of Catalytically Active Au Core─Pd Shell Nanoparticles Supported on Alumina - Feng, Yanyue; Schaefer, Andreas; Hellman, Anders; Di, Mengqiao; Härelind, Hanna; Bauer, Matthias; Carlsson, Per-Anders (Langmuir)
A two-step seeded-growth method was refined to synthesize Au@Pd core@shell nanoparticles with thin Pd shells, which were then deposited onto alumina to obtain a supported Au@Pd/Al2O3 catalyst active for prototypical CO oxidation. By the strict control of temperature and Pd/Au molar ratio and the use of l-ascorbic acid for making both Au cores and Pd shells, a 1.5 nm Pd layer is formed around the Au core, as evidenced by transmission electron microscopy and energy-dispersive spectroscopy. The core@shell structure and the Pd shell remain intact upon deposition onto alumina and after being used for CO oxidation, as revealed by additional X-ray diffraction and X-ray photoemission spectroscopy before and after the reaction. The Pd shell surface was characterized with in situ infrared (IR) spectroscopy using CO as a chemical probe during CO adsorption–desorption. The IR bands for CO ad-species on the Pd shell suggest that the shell exposes mostly low-index surfaces, likely Pd(111) as the majority facet. Generally, the IR bands are blue-shifted as compared to conventional Pd/alumina catalysts, which may be due to the different support materials for Pd, Au versus Al2O3, and/or less strain of the Pd shell. Frequencies obtained from density functional calculations suggest the latter to be significant. Further, the catalytic CO oxidation ignition-extinction processes were followed by in situ IR, which shows the common CO poisoning and kinetic behavior associated with competitive adsorption of CO and O2 that is typically observed for noble metal catalysts.
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos, Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas; Grundmeier, Guido (Applied Surface Science)
Near ambient pressure XPS in nitrogen atmosphere was utilized to investigate gas-solid interactions within porous SiO2 films ranging from 30 to 75 nm thickness. The films were differentiated in terms of porosity and roughness. The XPS N1s core levels of the N2 gas in presence of the SiO2 samples showed variations in width, binding energy and line shape. The width correlated with the surface charge induced in the dielectric films upon X-ray irradiation. The observed different binding energies observed for the N1s peak can only partly be associated with intrinsic work function differences between the samples, opening the possibility that the effect of physisorption at room temperature could be detected by a shift in the measured binding energy. However, the signals also show an increasing asymmetry with rising surface charge. This might be associated with the formation of vertical electrical gradients within the dielectric porous thin films, which complicates the assignment of binding energy positions to specific surface-related effects. With the support of Monte Carlo and first principles density functional theory calculations, the observed shifts were discussed in terms of the possible formation of transitory dipoles upon N2 physisorption within the porous SiO2 films.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Enhancement of the delamination resistance of adhesive film coated surface laser melted aluminum 7075-T6 alloy by aminophosphonic acid adsorption - Vieth, P.; Garthe, M.-A.; Voswinkel, Dietrich; Schaper, Mirko; Grundmeier, Guido (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; Kollmann, S.; Carlet, M.; de los Arcos de Pedro, Maria Teresa (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Tribo-mechanical properties and biocompatibility of Ag-containing amorphous carbon films deposited onto Ti6Al4V - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Franke, Carlo; Kokalj, David; Stangier, Dominic; Filor, Viviane; Mateus-Vargas, Rafael Hernán; Oltmanns, Hilke; Kietzmann, Manfred; Meißner, Jessica; Hein, Maxwell; Pramanik, Sudipta; et al. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Effects of KF and RbF treatments on Cu(In,Ga)Se2-based solar cells: A combined photoelectron spectroscopy and DFT study - Majumdar, I.; Sahoo, S.K.; Parvan, V.; Mirhosseini, Hossein; Chacko, B.; Wang, Y.; Greiner, D.; Kühne, Thomas; Schlatmann, R.; Lauermann, I. (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Controlling Self-Assembly with Light and Temperature - Carl, Nico; Müller, Wenke; Schweins, Ralf; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin; Büngeler, Anne; Kielar, Charlotte; Keller, Adrian; Strube, Oliver; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Secondary Particle Formation during the Nonaqueous Synthesis of Metal Oxide Nanocrystals - Stolzenburg, Pierre; Hämisch, Benjamin; Richter, Sebastian; Huber, Klaus; Garnweitner, Georg (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Silica Polymerization from Supersaturated Dilute Aqueous Solutions in the Presence of Alkaline Earth Salts - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Insight into the Final Step of the Supramolecular Buildup of Eumelanin - Büngeler, Anne; Hämisch, Benjamin; Huber, Klaus; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Gelled Lyotropic Liquid Crystals - Xu, Yang; Laupheimer, Michaela; Preisig, Natalie; Sottmann, Thomas; Schmidt, Claudia; Stubenrauch, Cosima (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Use of Eutectic Mixtures for Preparation of Monolithic Carbons with CO2-Adsorption and Gas-Separation Capabilities - Lopez Salas, Nieves; Jardim, E. O.; Silvestre-Albero, A.; Gutiérrez, M. C.; Ferrer, M. L.; Rodríguez-Reinoso, F.; Silvestre-Albero, J.; del Monte, F. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Mechanistic Studies of Silica Polymerization from Supersaturated Aqueous Solutions by Means of Time-Resolved Light Scattering - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Self-organization of nanospheres in trenches on silicon surfaces - Brassat, Katharina; Assion, Fabian; Hilleringmann, Ulrich; Lindner, Jörg K. N. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Structural Evolution in the Isotropic Channel of a Water–Nonionic Surfactant System That Has a Disconnected Lamellar Phase: A 1H NMR Self-Diffusion Study - Stubenrauch, Cosima; Kleinschmidt, Felix; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Impact of Sodium Polyacrylate on the Amorphous Calcium Carbonate Formation from Supersaturated Solution - Liu, J.; Pancera, S.; Boyko, V.; Gummel, J.; Nayuk, R.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

New experiments for the quantification of counterion condensation - Huber, Klaus; Scheler, Ulrich (Current Opinion in Colloid & Interface Science)
Keywords: Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Surfaces and Interfaces

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Size Determination of Shear-Induced Multilamellar Vesicles by Rheo-NMR Spectroscopy - Medronho, B.; Schmidt, Claudia; Olsson, U.; Miguel, M. G. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Defect Formation in a Nonionic Lamellar Phase - Medronho, B.; Rodrigues, M.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Evaluation of the Particle Growth of Amorphous Calcium Carbonate in Water by Means of the Porod Invariant from SAXS - Liu, J.; Pancera, S.; Boyko, V.; Shukla, A.; Narayanan, T.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Hydrogen-Bond-Induced Heteroassembly in Binary Colloidal Systems - Bayer, Frank M.; Hiltrop, Karl; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Reflection of femtosecond pulses from soft X-ray free-electron laser by periodical multilayers - Ksenzov, D.; Grigorian, S.; Hendel, S.; Bienert, F.; Sacher, Marc; Heinzmann, U.; Pietsch, U. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Shear-Induced Transitions between a Planar Lamellar Phase and Multilamellar Vesicles: Continuous versus Discontinuous Transformation - Medronho, B.; Shafaei, S.; Szopko, R.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Analysis of the Nucleation and Growth of Amorphous CaCO3 by Means of Time-Resolved Static Light Scattering - Liu, Jianing; Rieger, Jens; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Dielectric layers for organic field effect transistors as gate dielectric and surface passivation - Diekmann, T.; Pannemann, C.; Hilleringmann, Ulrich (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Structure−Property Relationship in Stimulus-Responsive Bolaamphiphile Hydrogels - Meister, Annette; Bastrop, Martin; Koschoreck, Sven; Garamus, Vasil M.; Sinemus, Thomas; Hempel, Günter; Drescher, Simon; Dobner, Bodo; Richtering, Walter; Huber, Klaus; Blume, Alfred (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shrinking of anionic polyacrylate coils induced by Ca2+, Sr2+ and Ba2+: A combined light scattering and ASAXS study - Schweins, R.; Goerigk, G.; Huber, Klaus (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

Confined phonons in glasses - A study by nuclear inelastic absorption and Raman scattering - Asthalter, T.; Bauer, Matthias; van Bürck, U.; Sergueev, I.; Franz, H.; Chumakov, A.I. (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

Aggregation of a Pseudoisocyanine Chloride in Aqueous NaCl Solution - Herzog, Bernd; Huber, Klaus; Stegemeyer, Horst (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Lyotropic Mesophases Next to Highly Efficient Microemulsions: A 2H NMR Study - Stubenrauch, Cosima; Frank, Christian; Strey, Reinhard; Burgemeister, Daniel; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Collapse of sodium polyacrylate chains in calcium salt solutions - Schweins, R.; Huber, Klaus (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

Model of Polydisperse Wormlike Stars and Its Application to Dyestuff Aggregates - Katzenstein, Armin; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Time-Resolved Recording of Ionic Dyestuff Aggregation by Static Light Scattering - Inglés, Sergio Escudero; Katzenstein, Armin; Schlenker, Wolfgang; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced States of Orientation of the Lamellar Phase of C12E4/Water - Müller, Stefan; Börschig, Claus; Gronski, Wolfram; Schmidt, Claudia; Roux, Didier (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Alignment of a Hexagonal Lyotropic Liquid Crystal as Studied by Rheo-NMR - Lukaschek, Michail; Grabowski, David A.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science